2015
DOI: 10.1186/s13287-015-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cell-based treatment for acute liver failure

Abstract: IntroductionAcute liver failure (ALF) is a highly lethal disease, for which effective therapeutic methods are limited. Although allogeneic liver transplantation is a viable treatment method for ALF, there is a serious shortage of liver donors. Recent studies suggest that stem cell transplantation is a more promising alternative. Hence, we investigate whether human adipose-derived stem cells (ASCs) have the therapeutic potential for ALF in this study based on the studies of rat models.MethodsSprague Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Nevertheless, organ shortages, disease progression and high medical cost limit the application of liver transplantation. Given this background, developing therapies other than transplantation has been greeted with growing enthusiasm . Consequently, as a result of its idiosyncratic and immune‐based pathogenesis, corticosteroids have been introduced to treat DILI, especially in severe cases who are more likely to develop ALF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, organ shortages, disease progression and high medical cost limit the application of liver transplantation. Given this background, developing therapies other than transplantation has been greeted with growing enthusiasm . Consequently, as a result of its idiosyncratic and immune‐based pathogenesis, corticosteroids have been introduced to treat DILI, especially in severe cases who are more likely to develop ALF.…”
Section: Discussionmentioning
confidence: 99%
“…Given this background, developing therapies other than transplantation has been greeted with growing enthusiasm. 23 Consequently, as a result of its idiosyncratic and immune-based pathogenesis, corticosteroids have been introduced to treat DILI, 24 especially in severe cases who are more likely to develop ALF. However, the efficacy of corticosteroids for DILI has still not been clearly elucidated to date and it is not routinely recommended for DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies proved that MSCs could differentiate into hepatocyte-like cells (HLCs) in vivo, considered as one of the mechanisms of MSCs in the treatment of liver failure [26,27]. While some experiments have suggested that MSCs cannot differentiate into HLCs after engrafting even if the improved survival, reduced alanine aminotransferase (ALT) and relieved liver injury [28]. These ndings demonstrate that the effective performance of MSCs in the treatment of liver failure is not just dependent on the supplementing exogenous hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…They include a type of multipotent adult stem cells isolated from adipose tissue and have the capacities of self-regeneration and differentiation into various cell lineages [9,10]. Both BMSCs and ADSCs have common biological properties such as cell surface markers, gene expression profile, immunosuppressive features, and differentiation capacity, but ADSCs have more proliferative capacity than that of BMSCs [11]. ADSCs have been used in a recent technique for wound repair, regeneration, and tissue engineering procedures because the adipose tissue is easy to gain and process; in addition, the isolated cells expand rapidly and differentiate into different cell types in vitro [12][13][14].…”
Section: Introductionmentioning
confidence: 99%